Clinical and Genetic Analysis of Myoclonus-Dystonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Eighty-six myoclonus-dystonia (M-D) index patients from the Dutch national referral center underwent clinical and genetic evaluation in a study at University of Amsterdam, and other centers in the Netherlands and Belgium.